Justification, evaluation and critique in the study of organizations : contributions from French pragmatist sociology - Cloutier, Charlotte; Gond, Jean-Pascal; Leca, Bernard (Research in the sociology of organizations, 2017)
This volume explores how mobilizing Boltanski and Thévenot's economies of worth framework, and its associated concepts of justification, evaluation and critique, help address questions regarding the premises and dynamics of coordinated action, both within and across organizations, and by so doing help advance our understanding.